How Privacy Killed Katz: A Tale of Cognitive Freedom and the Property of Personhood as Fourth Amendment Norm - Halliburton, Christian (2009)
This article seeks for the very first time to inform that debate with a notion of property as an essential aspect of human identity in a mash-up of sorts that might be called Fourth Amendment jurisprudence meets the Radinesque Property of Personhood. Using an expanded version of the notion of property developed by Professor Margaret Radin in her pioneering work Property and Personhood, the Fourth Amendment must contend with the social reality that some aspects of ownership or entitlement to property, and some level of vindication of those interests, are essential to the formation and viability of complete human beings. Such an expanded notion of property avoids all the pitfalls associated with the trespassory property concepts criticized in Katz. This article expounds on the expanded notion of property, and Part I briefly traces the Fourth Amendment's historical approach of analyzing Fourth Amendment claims by reference to property rights and common law prohibitions on trespass against property. Part I also presents the Katz Court's privacy-based response to that historical approach. While this part explores the possibility that Katz does not stand for the proposition that the Fourth Amendment deals only with privacy to the exclusion of property, it concludes by emphasizing that, at present, privacy rules the Fourth Amendment roost. Part II takes on this privacy-centric Fourth Amendment and considers the extent to which it might preserve the mental solitude and freedom of thought that is fundamental to so many of our personal and social dynamics. Following this practical analysis, which reaches negative conclusions about privacy's utility, are further discussions of the normative weakness of the privacy regime and of the jurisprudential sleight-of-hand necessary to support it. Part III then presents the argument that if we did demote (but not entirely discard) privacy, and installed a robust respect for the property of personhood in its place, it would restore the vitality and authenticity of the Fourth Amendment. This final part develops Radin's personal property model, offers several conceptual enhancements to that model necessary to adapt it to the Fourth Amendment, and then applies this enhanced theory to CCTs and a series of other Fourth Amendment issues in order to demonstrate the value of this proposed reform